Penggunaan Tanda Tangan Digital Tersertifikasi Untuk Persuratan Di Sekolah Berbasis Android - Fendri Martadinata; Hakim, Ridwan (jurnal kesehatan terapan sains dan teknologi, 2024)
Abstract : Along with the development of information technology, the world of education is faced with the need to improve efficiency and security in managing document administration. This study aims to explore the benefits and implementation of the use of digital signatures in the school administration system. Certified digital signatures have the advantage of guaranteeing the authenticity and integrity of documents, as well as reducing paper use, thus supporting operational efficiency. This correspondence often causes obstacles because this activity requires a lot of time to do. In addition, the signing process is not fast because the signatory is sometimes not there. The solution to the above problems requires the use of a correspondence application using a certified digital signature. Android-based applications that support digital signatures allow educators and administrative staff to access, sign, and send documents practically, safely and signing can be done anywhere and anytime. And this study uses data collection techniques using qualitative methods and software development methods using waterfall.